Training Of Trainer (TOT) Pada Caregiver Tentang Ambulasi Dan Mobilisasi Di Panti Werdha Marfati Tangerang - Imam Saguh Mardiono; Laily Maftuhah; Lidia Rosaria; Mugiyanto Mugiyanto; Nur Hafidiani; Rini Handayani; Siti Mahdiah; Susi Aria Mensi; Titi Sabariyah; Siti Robeatul Adawiyah; Regina Windyastuti (Institut Nalanda, 2024)
Mobility, the ability to move freely, easily, rhythmically and purposefully in the environment is a very important part of life. Individuals must move to protect themselves from trauma and to fulfill their basic needs (Asmadi, 2017). Mobility is very important for the independence of individuals who are not able to move totally as vulnerable and dependent as a baby. Using counseling methods, question and answer, roleplay with additional media properties. Training of Trainer activities means that participants listen and are orderly in the process of delivering material by the presenter and participants are able to practice correctly how to ambulate and mobilize with a wheelchair, walker and cane. after the training, participants know the definition, objectives, types and How to ambulate and mobilize elderly people who are on bed rest, namely how to ambulate and mobilize using a wheelchair, walker and cane.